Consistent thermodynamic modeling of H2O–HCl–KOH–KCl between 200 K and 1, 000 K. (31st December 2022) - Niazi, Sepideh; Nygård, Heidi S.; Reis, Bruno; Baben, Moritz to
Highlights: Thermodynamic modeling of an entire reciprocal system using a single subregular model for the liquid phase. Thermodynamic modeling of the liquid solution spanning from water to liquid acid and base, and liquid salt as a single phase. Excellent representations of the phase diagrams and properties of the liquid phase in all binary sub-systems. Abstract: Over the last few decades, thermochemical databases for aqueous solutions and for high-temperature salt solutions have been developed separately from each other. This is largely due to the fact that the models used for the liquid phases are inconsistent. However, there is interest in highly concentrated aqueous solutions, as well as in the hydrolysis of salt melts, closing the gap between the two communities. Here, the liquid phase was consistently modeled, covering the complete composition space between H2 O, HCl, KOH, and KCl at temperatures between 200 K and 1, 000 K. Thermodynamic modeling of phase equilibria in the KCl–K2 O–HCl–H2 O reciprocal system was carried out using an associate solution model for the liquid phase, spanning from water to pure liquid acid and base, and liquid salt. Using the Calphad technique, the H2 O–KCl, H2 O–HCl, H2 O–K2 O, and KOH–KCl binary systems were critically assessed. While the model does not cover classical aqueous thermochemical properties (pH and osmotic coefficient), an excellent representation of phase diagrams and heat of reactions was achieved.